CHARACTERIZATION OF THE Α-AMYLASE INHIBITOR FROM THE SEEDS OF MACROTYLOMA UNIFLORUM AND VIGNA UNGUICULATA - LAXMI H. GUPTA; ASHOK CHOUGALE; MAHESH KULKARNI; SUSHMA G. SABHARWAL (International Journal of Pharma and Bio Sciences, 2013)
α-amylase inhibitors were purified and characterized from the seeds of Macrotyloma uniflorum (MUAI) and Vigna unguiculata (VUAI). MUAI was purified using CM-cellulose column while VUAI was purified using Poros HS-50 column followed by gel filtration on Sephadex G-75 column. The molecular weights of MUAI and VUAI as determined by gel filtration were 26.91 kD and 21.89 kD respectively. Both MUAI and VUAI were found to be glycoproteins. The secondary structure of both MUAI and VUAI was determined using circular dichroism studies at different pH and different temperatures. MUAI and VUAI were identified using MALDI-TOF/TOF and LC MSE analysis respectively.